Impact of Moringa oleifera Meal (MOM) Inclusion in Diet on Haemato-Biochemical Profile of Growing Surti Kids - Pandey, Anushri; Modi, Rakesh J; Lunagariya, Pravin M; Islam, Manzarul (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present research work was intended to assess the haemato-biochemical profile of 6-8 months old 18 growing Surti kids by utilizing the three diverse concentrations of Moringa oleifera meal (0%, 25% and 50%) by weight premix in concentrate part of feed. The diets were offered for 14 weeks to the experimental kids, which were randomly divided into three groups of six kids each, i.e., 4 females and 2 males in each group. The haemato-biochemical parameters were measured individually at the beginning (Day 0), mid (Day 49) and end (Day 98) of the experiment. Results showed that haemoglobin and serum total protein, ALT (Alanine transaminase), AST (Aspartate transaminase), urea, glucose, calcium and phosphorus showed no significant difference, while serum creatinine, catalase, and SOD (Superoxide dismutase) activity differed significantly (p<0.05) at 0, 25 and 50% Moringa oleifera meal (MOM) inclusion. However, all the haemato-biochemical and oxidative parameters fell under the normal physiological range in all the treatment groups. It was concluded that inclusion of Moringa oleifera meal up to 50% inclusion rate did not cause any adverse effect on the haemato-biochemical profile of Surti kids when fed for 14 weeks duration, while antioxidant levels in blood improved during the experiment, resulting into better immunity of growing kids. Thus, the MOM could be used to improve livestock system of small ruminant without any adverse effect on haemato-biochemical profile.